Evaluation of Trust Algorithm in a Mobile Ad-Hoc Network Using Artificial Engineering - et. al., Dr. T. Kowsalya , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A MANET network is made up of wireless nodes which operate without a defined structure, the arrangement of existing devices does not have any ministerial or control entity . the management tasks are carried out by the teams which are in the network, therefore a MANET network is said to be a managed network. As there is no infrastructure, such as, the bandwidth, availability, input error rate, among others, depend exclusively on the behaviour of the network users. This work presents a functional solution, which decreases the energy consumption in MANET networks, implemented using game theories and genetic algorithms solution. The evaluation of the pay-as-you-go strategy from the modified prisoner dilemma was shown to be an easy to implement and interpret tool for the network equipment. The processes of generation, combination and mutation of strategies demonstrated the in-centive of cooperation in the network, observed in the increase of the average confidence of the nodes, a very high value. The intervention of the protocol with the use of genetic algorithms, demonstrated ot be a form of implementation of solutions for problems of multiple agents, the increase in the evaluation of trust of the nodes was observed, which can be interpreted as a convergence of the nodes to cooperate. The results obtained in the simulations carried out show the functioning of the algorithm implemented and the functionality of the network after its implementation.